하사근 궤도와 주위 안구구조의 관계에 대한 형태계측학적 연구 - 이승혁; Seung Hyuck Lee; 이종복; Jong Bok Lee; 정인혁; In Hyuk Chung; 임승정; Seung Jung Lim (Daihan angwa haghoi jabji, 2000)
하사근 후전술은 후전량에 따른 후전위치 결정방법이 술자마다 다르고 한국인을 대상으로 한 해부학적 연구자료가 없으므로 정확한 후전위치를 쉽게 찾을 수 있는 방법을 알아보고자 하였다. 한국사람의 사후에 얻어진 눈 31개를 재료로 하여 외안근과 공막을 노출한 후 하사근의 주위 구조인 하직근과 외직근의 부착부, 하이측 또아리정맥의 공막출구에서 하사근의 주행궤도까지의 거리를 측정하여 다음과 같은 결과를 얻었다.하사근의 8 mm 후전지점은 외직근 부착부의 하연을 기준으로 뒤로 6.9±0.6 mm, 아래로 4.6±1.5 mm 였고 10 mm 후전지점은 각각 5.6 ±1.3 mm, 6.6±2.0 mm, 12 mm 후전지점은 4.7±0.7 mm, 8.4±1.5 mm, 14 mm후전지점은 3.7±1.7 mm, 9.5±2.0 mm에 해당되었다. 하사근의 8 mm 후전지점은 하직근 부착부의 외연을 기준으로 뒤로 3.5±0.6 mm, 외측으로 6.5±0.8 mm 였고, 10 mm 후전지 점은 각각 2.9±1.0 mm, 3.6±1.0 mm, 12 mm 후전지점은 3.3±0.6 mm, 2.3±0.6mm, 14 mm 후전지점은 3.0±1.5 mm, 0.5±0.9 mm에 해당되었다. 14 mm 후전지점과 하이측 또아리정맥의 공막출구까지의 거리는 평균 6.6±1.4 mm(범위 4~9 mm)였다. 하사근 후전지점에서 하직근과 외직근 부착부까지의 측정거리는 양안에서 통계학적으로 의미있는 차이를 보이지 않아 하사근의 주행궤도는 양쪽눈에서 차이가 없음을 알 수 있었다. 이상의 결과들로써 한국인의 하사근 주행궤도와 주위 안구구조의 관계를 밝혀 후전술시 공막재 부착지점에 대한 참고자료가 될 것으로 생각한다(한안지 41:2124~2131,2000). There are no known data of recession point of inferior oblique muscle(IO) in Korean. The purpose of this study was to determine the accurate reinsertion point of IO and compare the previous data with ours. Thirty-one Korean cadaver orbits were dissected to expose the full length of extraocular muscles and sclera, and then we measured the length from the recession point of IO to lateral edge of insertion of inferior rectus muscle(IR) and to inferior edge of insertion of lateral rectus muscle(LR). Eight mm recession point of IO was measured 6.9±0.6 mm posteriorly along the inferior border of LR from inferior edge of LR insertion, and 4.6±1.5 mm inferiorly. For 10 mm recession, it was 5.6±1.3 mm posteriorly and 6.6±2.0 mm inferiorly. For 12 mm recession, it was measured 4.7±0.7 mm posteriorly and 8.4±1.5 mm inferiorly. And for 14 mm recession, it was 3.7±1.7 mm posteriorly and 9.5±2.0 mm inferiorly. Eight mm recession point of IO was measured 3.5±0.6 mm posteriorly along the lateral border of IR from the lateral edge of IR insertion, and 6.5±0.8mm laterally. For 10 mm recession, it was 2.9±1.0 mm posteriorly and 3.6±1.0 mm laterally. For 12 mm recession, it was measured 3.3±0.6 mm posteriorly and 2.3±0.6 mm laterally. For 14 mm recession, it was 3.0 ±1.5 mm posteriorly and 0.5 ±0.9 mm laterally. The cord length on a straight line from 14 mm recession point of IO to the scleral exit site of the inferior temporal vortex vein was 6.6±1.4 mm(range 4~9 mm). The distance from IO recession points to IR insertion site and to LR insertion site were compared in ten paired eyes, and the difference was not statistically significant(p＞0.05). We made anatomical studies to evaluate the proper placement of scleral reinsertion site of IO in Korean(J Korean Ophthalmol Soc 41:2124~2131,2000).